"Ecotourism” and “Sustainability”: A Bibliometrics Analysis using Biblioshiny and VOS viewer - SINGH, Amrik; KAPOOR, Nihal; KUMAR, Abhishek; SHARMA, Rajan; KUMAR, Manoj (Journal of Environmental Management and Tourism; Vol 16 No 1 (2025): JEMT Volume XVI, Issue 1(77), Spring 2025DO - 10.14505/jemt.v16.1(77).04, 2025)
This study presents a bibliometric analysis of research on sustainability in ecotourism, highlighting global trends, key themes, and emerging areas. Using databases like Scopus 1993–2024 till the date 10 th December. Publications were analyzed to identify influential authors, institutions, and journals. The findings reveal a growing interest in sustainable practices, and biodiversity conservation within ecotourism. This Study uses Bibliometrics analysis (Biblioshiny), and VOS viewer software to identify the main developments. To achieve this goal in the "Scopus" database "Ecotourism Sustainability" keyword searched. Overall, 2849 articles were discovered. After applying the filter to the English language only 2741 articles were left. Again, we use a filter to get access to articles only and are left with 2275 articles. Although we need the articles of the journals only and get 2261 articles. After that, we narrowed our research to 2 subject areas social science and business, management and accounting we got 1752 articles. out of these 12 articles are in press so after excluding these articles we finalize our research to 1740 articles. The findings highlight annual publication trends, most relevant journals, top Nations, Journals and co-citation, co-occurrence and thematic analysis. The findings show that the most relevant journal is “Sustainability (Switzerland)”, Australia is the leading country and “Sustainability” is the most cited keyword. The results show the growing interest of researchers in the emerging field of ecotourism and sustainability and more attention is needed to enhance theoretical and empirical exploration of a domain in future.